BIOKONSENTRASI LOGAM BERAT TEMBAGA (Cu) DAN POLA KONSUMSI IKAN MUJAIR DI WILAYAH DANAU RAWAPENING - Ailsa Devina Rosahada; Budiyono Budiyono; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
People near Rawapening usually make a living by doing agricultural, livestock and fishing in Rawapening. However, some of these activities can increare the copper pollution in the lake's water. On the other hand, water qualities are one of the most important factors in fishery, because it can have an effect to human’s health. The aim of this research is to know the bioconcentration value of copper in Oreochromis mossambicus at Rawapening and maximum limit of daily consumption of fish which is safe for human. Sampling was done by purposive sampling by buying catches to fishermen directly and through collectors. Measurement of copper concentration in water and fish used the Atomic Absorption Spectrophotometry method. Concentration of copper in water at Rawapening has exceeded the quality standard of government regulation in Indonesia Number 82 of 2001 which was equal to 0.063 mg/l. Consentration of copper in Oreochromis mossambicus has exceeded the quality standard of Indonesia National Standard which was equal to 0.6 mg/kg. Bioconcentration of Oreochromis mossambicus in Rawapening was equal to 10.26. The BCF category the Cu metals fall into the category of low accumulation. The maximum daily consumption limit of catch fish in Rawapening was 3.280 g/day for adult women and 3.900 grams/day for adult men. The average consumption of Rawapening community was 218±37 grams/day and the median value 225±37 grams/day. This research can be concluded that copper have low category accumulation and average daily consumption of people near Rawapening remains below the safe limit.